RANCANG BANGUN APLIKASI TRANSAKSI PULSA ELEKTRONIK TELEPON SELLULAR BERBASIS ANDROID - Yuliana, Eka; -, Yulmaini (Jurnal Informatika, 2016)
Refill of electronic phone credit is a method to do an electronic phone credit transaction to a hand phone number through electronic. The refill of phone credit through an electronic can be done by sending short messages using short message service (SMS) technology. The message will be sent with the format determined by the phone credit server. Every phone credit server has a different format or operator code. The seller (user) has to memorize specific codes so that it is apt to making errorssuch as in inputting the operator code or the amount of phone credit inputted is not correct. The application design used the development of software waterfall and Blackbox testing as the testing method. The phases done at the waterfall method are analysis, design, implementation, testing and maintenance. This application has several advantages such as platform used was based on android. Another advantage was the integration of other facilities in this application. Besides as an application of phone credit application, there was useful information like phone credit information, phone credit transaction information and also daily or weekly phone credit information can be obtained easily. Users can select the available content menu in the application such as phone credit menu, balance ticket or change the pin without having to type the manual format such as having to memorize the code of each operator, so the level of errors in this case human error can also be minimized.Keywords:Phone Credit Transaction, Android, Waterfall.